1999
DOI: 10.1142/s0192415x99000197
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Acupuncture at Nei-Kuan on Left Ventricular Function in Patients with Coronary Artery Disease

Abstract: Effect of acupuncture at Nei-Kuan (EH-6) on left ventricular ejection fraction (LVEF) was examined in 22 patients with angiographically proved coronary artery disease (CAD) and 22 normal subjects. Serial equilibrium radionuclide angiography was done to measure LVEF at 4 different times (at baseline, at 1 to 15 minutes, and 16 to 30 minutes during acupuncture, and immediately after acupuncture). One week later, each patient had an identical imaging protocol with acupuncture performed at a dummy point. Our resul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
19
0
2

Year Published

2004
2004
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(21 citation statements)
references
References 6 publications
0
19
0
2
Order By: Relevance
“…Interest in application of acupuncture as an alternative medical management in the western countries has increased over the last two decades. Acupuncture at the NeiguanJianshi acupoints (P5-P6, overlying the median nerve) is used specifically to treat cardiovascular diseases, one of greatest causes of death around the world (Ho et al, 1999;Li et al, 1998;Lin et al, 2001). Our previous studies have demonstrated that electrical stimulation of the P5-P6 acupoints significantly attenuates sympathoexcitatory pressor responses elicited by chemical and mechanical stimulation of viscera, such as gallbladder and stomach (Li et al, 2001 and, suggesting that electroacupuncture (EA) exerts its influence by modulating sympathetic activity (Tjen-A- Looi et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…Interest in application of acupuncture as an alternative medical management in the western countries has increased over the last two decades. Acupuncture at the NeiguanJianshi acupoints (P5-P6, overlying the median nerve) is used specifically to treat cardiovascular diseases, one of greatest causes of death around the world (Ho et al, 1999;Li et al, 1998;Lin et al, 2001). Our previous studies have demonstrated that electrical stimulation of the P5-P6 acupoints significantly attenuates sympathoexcitatory pressor responses elicited by chemical and mechanical stimulation of viscera, such as gallbladder and stomach (Li et al, 2001 and, suggesting that electroacupuncture (EA) exerts its influence by modulating sympathetic activity (Tjen-A- Looi et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…Clinically, EA at the NeiguanJianshi (P5-6) acupoints has been used to treat cardiovascular diseases in Eastern and, more recently, Western countries (5,21,41). We and others have demonstrated that EA at P5-6 acupoints overlying the median nerve on the wrist modulate blood pressure elevation evoked by gastric distension (GD) in rats (27) or by gallbladder stimulation in cats (50) through a long-loop neural pathway, extending from the arcuate nucleus (ARC) in the hypothalamus to the ventrolateral periaqueductal gray (vlPAG) in the midbrain and, ultimately, to the rostral ventrolateral medulla (rVLM) (13,26,50,58).…”
mentioning
confidence: 99%
“…Chinese and European physicians have suggested that EA is effective in alleviating certain cardiovascular diseases and their symptoms, including hypertension, arrhythmias, and angina (1,12,19,26,48,49,56). One well-recognized set of acupoints, Jianshi-Neiguan (located along the pericardial meridian, P5-P6), is positioned directly over the median nerve on the wrist and is used frequently to treat symptomatic coronary heart disease (12,26,37). Our laboratory has developed a feline model of a partial coronary artery occlusion to study the mechanism of EA's cardiovascular influence during stimulation of the P5-P6 acupoints as well as the median nerve directly.…”
mentioning
confidence: 99%